The Effect Of Consumption Of The Heart Of Banana On The Production Of Breast Milk In Breastfeeding Mother - Ita Rosita -; Triana Indrayani; Cholisah Suralaga (UrbanGreen, 2020)
The Coverage Of Exclusive Breastfeeding Nationally In 2018 Was 67%, In Banten Province In 2019 It Was 71.32%, In Pandeglang Regency It Was 70.93% And In Saketi Health Center It Was 66.90%. This Coverage Is Still Far From The National Target Of 80%. The Results Of Interviews With 10 Breastfeeding Mothers In The Saketi Health Center Work Area, It Was Found That 60% Of Them Had Problems With Milk Production. To Determine The Effect Of Consumption Of Kepok Banana Heart Stew On Breast Milk Production In Breastfeeding Mothers In The Saketi Community Health Center, Pandeglang Regency In 2020.The Research Design Used A Quasi Experimental One Group Pretest And Posttest Design. The Sample In The Study Was 50 Respondents. The Sampling Technique Used Total Sampling. Data Were Collected Using Observation Sheets. Parametric Test Using Paired T-Test.The Average Milk Production Of Breastfeeding Mothers Before Consuming Kepok Banana Heart Stew (Pretest) Was 3.40 And After Consuming Kepok Banana Heart Stew (Posttest) The Average Value Of Breastfeeding Mother's Milk Production Was 8.32. The Statistical Test Results Obtained The Sig Value. (2-Tailed) = 0.000 (<Α 0.05), Meaning That There Is A Significant Effect Of Consumption Of Kepok Banana Heart Stew On Breast Milk Production In Breastfeeding Mothers At Saketi Health Center, Pandeglang Regency In 2020.